2023
DOI: 10.1109/ojcoms.2023.3253643
|View full text |Cite
|
Sign up to set email alerts
|

Broadband Connectivity for Handheld Devices via LEO Satellites: Is Distributed Massive MIMO the Answer?

Abstract: Significant efforts are being made to integrate satellite and terrestrial networks into a unified wireless network. One major aspect of such an integration is the use of unified user terminals (UTs), which work for both networks and can switch seamlessly between them. However, supporting broadband connectivity for handheld UTs directly from low Earth orbit (LEO) satellite networks is very challenging due to link budget reasons. This paper proposes using distributed massive multiple-input multiple-output (DM-MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…It has been shown that with adequately designed algorithms, MIMO is a promising approach to achieving significant performance gains. For distributed MIMO techniques in satellite networks, the authors of [34] and [35] explore the LEO satellite cooperation to support handheld devices using cross-layer design, artificial intelligence (AI)based implementation, and broadband connectivity, showing superior performance compared to CMM modes. While satellite networks have shown significance in the QoS for ground users, this complete dependence on satellite works neglects potential communication services brought by TN.…”
Section: A Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been shown that with adequately designed algorithms, MIMO is a promising approach to achieving significant performance gains. For distributed MIMO techniques in satellite networks, the authors of [34] and [35] explore the LEO satellite cooperation to support handheld devices using cross-layer design, artificial intelligence (AI)based implementation, and broadband connectivity, showing superior performance compared to CMM modes. While satellite networks have shown significance in the QoS for ground users, this complete dependence on satellite works neglects potential communication services brought by TN.…”
Section: A Related Workmentioning
confidence: 99%
“…We consider using ZFBF strategy with equal power allocation across the satellite beams to null interference from/to intra-satellite users, while the MRTBF strategy is utilized at terrestrial BSs to enhance the desired signal strength of the associated user with a pointing beam 2 . Considering complicated communication environment and random distributions of users and BSs, we consider equal power allocation for LEO satellites and BSs and roundrobin scheduling for all users to obtain the basic outcomes as an average situation.…”
Section: B Downlink Transmissionmentioning
confidence: 99%
See 3 more Smart Citations